1985
DOI: 10.1073/pnas.82.10.3528
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort-loop positive feedback of corticotropin (ACTH)-releasing factor to enhance ACTH release in stress.

Abstract: Previous experiments have shown that intraventricular injection of ovine corticotropin (ACTH)-releasing factor (oCRF) in doses too low to elevate plasma ACTH by direct action on the pituitary does not lower plasma ACTH, suggesting that the peptide lacks a negative ultrashortloop feedback action to suppress its own release under resting conditions. The present study was performed to determine whether oCRF has any action to alter CRF release in stress.The peptide was injected into the third ventricle or external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…This effect may be due to a blockade of the recently shown ultrashort loop positive feedback of CRF to enhance its own release during stress (16). It is clear that antisera injected into the ventricle can be taken up via the adjacent hypothalamic tissue and act there (17).…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be due to a blockade of the recently shown ultrashort loop positive feedback of CRF to enhance its own release during stress (16). It is clear that antisera injected into the ventricle can be taken up via the adjacent hypothalamic tissue and act there (17).…”
Section: Discussionmentioning
confidence: 99%
“…We pool the integrated influences of glutamate, CRH, and ACTH from different brain regions in one molecular cue of the brain/pituitary compartment named Y (with a physiological interpretation as plasma ACTH) and suppose that the concentration y gives a positive stimulus on Z. This pooling of the CRH and ACTH compartments can be physiologically justified by the strong and fast synchrony between these hormones [20]. Additionally, Drolet et al showed that effects on CRH may be directly observed through the concentration of ACTH [21].…”
Section: Modelmentioning
confidence: 99%
“…These apparently paradoxical reports of the effects of opioids within and between species may be reconciled by proposing that, if these actions reflect short loop feedback inhibition of CRH synthesis, then the effects may be concentration-dependent, such that increasing central concentrations of POMC peptide products may stimulate CRH expression to a maximum point beyond which POMC peptides become inhibitory. The observed ability of CRH to either stimulate (Ono et al 1985) or inhibit (Calogero et al 1988b) its own release suggests a mechanism whereby -endorphin might exert opposing concentration-dependent effects upon the HPA axis, mediated by CRH.…”
Section: -Endorphinmentioning
confidence: 99%